Conceptions of Learning, Well-being, and Creativity in Older Adults - Rosa Cera; Carlo Cristini; Alessandro Antonietti (LED Edizioni Universitarie, 2018)
The goal of this study is to investigate the conceptions of learning shared by older adults and to assess the relationships of such conceptions with creativity and satisfaction with life. A sample of 322 older adults (mean age = 72 years) attending Universities of the Third Age were administered the shortened version of a questionnaire aimed at capturing opinions and feelings associated to learning, a task from the Torrance Tests of Creative Thinking, and the Satisfaction with Life Scale. Age, gender, schooling, occupation, marital status, and hobbies of the participants were taken into account. Factorial analyses showed that different conceptions of learning can be identified and that some of them are affected by age, gender, and the hobbies practised by the respondents. Older participants and women considered learning as an interpersonal and focused process to a larger extent. Older participants expressed negative feelings about learning, whereas women expressed positive feelings. Satisfaction with life changed according to marital status with married people scoring higher. Creative skills decreased with age and were influenced by gender, level of education, marital status, and hobbies practiced. Associations between conceptions of learning and satisfaction with life and creativity emerged. Implications for interventions addressing older adults' well-being are discussed.